HUBUNGAN ANTARA POLA ASUH AUTORITATIF DENGAN PERILAKU PROSOSIAL PADA REMAJA - Vallahatullah Missasi (KOLABORATIF: Jurnal Isu Sosial dan Tinjauan Kebijakan, 2025)
This study aims to determine the relationship between authoritative parenting patterns and prosocial behavior in adolescents. Authoritative parenting patterns are characterized by a combination of high demands and high responsiveness, which are believed to be able to form positive social characters. The sample in this study was 100 adolescents with an age range of 13–18 years who were selected using purposive sampling techniques. The method used in this study is a quantitative research method with measuring instruments in the form of an authoritative parenting pattern scale and a prosocial behavior scale. The results of the analysis showed a significant positive relationship between authoritative parenting patterns and adolescent prosocial behavior (r = 0.58, p <0.01). The results of this study indicate that the better the level of authoritative parenting patterns applied by the mother, the better the tendency of prosocial behavior in adolescents